PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS BUDAYA JAWA PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD NEGERI 104281 NOGO REJO - risti, Diahyu; Sutarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The type of research conducted is Research and Development (R&D) Research and Development is one of the research methods applied to produce a product as well as test its validity so that it is suitable for use The ADDIE model consists of five steps in its implementation, namely: analysis, design, development, implementation, and evaluation The subjects in this study are grade IV students of SD Negeri 104281 Nogo rejo for the 2024 school year, Material Experts, Media Experts and Learning Experts Meanwhile, the object of this study is Javanese culture-based interactive learning media in the Indonesian subject of grade IV elementary school students. The product developed in this study is an interactive learning media based on Javanese culture. The existence of Javanese culture-based interactive learning media can make learning more effective, more interesting, and stimulate students' interest. Based on the data from the results of the media feasibility evaluation from the input of material expert reviewers with a percentage appropriateness of 84%, media expert reviewers with a percentage appropriateness of 100%, grade IV teacher responses with a percentage appropriateness of 85,3%, and student responses with a percentage appropriateness of 85,5%, the development of Javanese culture-based interactive learning media in Indonesian lessons developed was stated as "Very Feasible" to be used as a learning medium in grade IV of elementary school. Based on the discussion above, it can be concluded that the Javanese culture-based interactive learning media product in the Indonesian language lesson developed by the researcher was declared Very Feasible and there was no revision by expert reviewers and the Javanese culture-based interactive learning media was very feasible to be used as a learning medium.